2022
DOI: 10.3389/fnmol.2022.928587
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in CGRP Regulation and Function in the Amygdala in a Rat Model of Neuropathic Pain

Abstract: The amygdala has emerged as a key player in the emotional response to pain and pain modulation. The lateral and capsular regions of the central nucleus of the amygdala (CeA) represent the “nociceptive amygdala” due to their high content of neurons that process pain-related information. These CeA divisions are the targets of the spino-parabrachio-amygdaloid pain pathway, which is the predominant source of calcitonin gene-related peptide (CGRP) within the amygdala. Changes in lateral and capsular CeA neurons hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 146 publications
(232 reference statements)
1
23
0
Order By: Relevance
“…Chronic pain exhibits a higher prevalence in women than in men (1). Over the past years, preclinical studies have highlighted several sexual dismorphism in pain mechanisms (3335), notably at the amygdala level (36). ,Thus, we sought to determine whether amygdala mGlu 4 activation can also modulate neuropathic pain symptoms in female mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic pain exhibits a higher prevalence in women than in men (1). Over the past years, preclinical studies have highlighted several sexual dismorphism in pain mechanisms (3335), notably at the amygdala level (36). ,Thus, we sought to determine whether amygdala mGlu 4 activation can also modulate neuropathic pain symptoms in female mice.…”
Section: Resultsmentioning
confidence: 99%
“…Chronic pain exhibits a higher prevalence in women than in men (1). Over the past years, preclinical studies have highlighted several sexual dismorphism in pain mechanisms (33)(34)(35), notably at the amygdala level (36).,Thus, we sought to determine whether amygdala mGlu 4 activation can also modulate neuropathic pain symptoms in female mice. To that aim, we assessed the potential modulation of neuropathic pain symptoms following activation of mGlu 4 by the agonist LSP4-2022 in the right or left amygdala on female mice suffering from peripheral mononeuropathy in their left hind paw.…”
Section: Activation Of Mglu 4 In the Amygdala Also Relieves Neuropath...mentioning
confidence: 99%
“…Chronic pain exhibits a higher prevalence in women than in men [9]. Over the past years, preclinical studies have highlighted several sexual dismorphisms in pain mechanisms [33,36,5] notably in the amygdala [34]. Thus, we sought to determine whether amygdala mGlu 4 activation can also modulate neuropathic pain symptoms in female mice.…”
Section: Activation Of Mglu 4 In the Amygdala Also Relieves Neuropath...mentioning
confidence: 99%
“…It has been suggested that the amygdala receives inputs from the parabrachial nucleus and mediates differentiated pain and affective responses in males and females (Sun et al, 2020 ). Calcitonin gene-related peptide 1 (CGRP1) receptors in the central nucleus of the amygdala (CeA) are involved in neuropathic pain-related amygdala activity and contribute to nociception in both sexes (Presto and Neugebauer, 2022 ). However, they elicit emotional-affective pain responses such as ultrasound onset and anxiety-like behaviors mainly in females (Neugebauer et al, 2020 ).…”
Section: Sex Differences In Neural Circuitsmentioning
confidence: 99%